Variation of tRNA modifications with and without intron dependency - Hayashi, Sachiko (Frontiers in Genetics, 2024)
tRNAs have recently gained attention for their novel regulatory roles in translation and for their diverse functions beyond translation. One of the most remarkable aspects of tRNA biogenesis is the incorporation of various chemical modifications, ranging from simple base or ribose methylation to more complex hypermodifications such as formation of queuosine and wybutosine. Some tRNAs are transcribed as intron-containing pre-tRNAs. While the majority of these modifications occur independently of introns, some are catalyzed in an intron-inhibitory manner, and in certain cases, they occur in an intron-dependent manner. This review focuses on pre-tRNA modification, including intron-containing pre-tRNA, in both intron-inhibitory and intron-dependent fashions. Any perturbations in the modification and processing of tRNAs may lead to a range of diseases and disorders, highlighting the importance of understanding these mechanisms in molecular biology and medicine.